Role Victimology To Victim Violence In House Ladder in Women - Vicki Dwi Purnomo; Syukron Abdul Kadir; Trisno Raharjo (Formosa Journal of Applied Sciences, 2023)
Victims of criminal acts of domestic violence must receive legal protection so that their rights can be fulfilled and provide assistance to give victims a sense of security. The problem in this research is the legal arrangement for victims of domestic violence. This research is law enforcement theory and justice theory. This study uses normative research methods. The results and discussion of this study regarding legal arrangements for victims of domestic violence. Based on the principle or theory of law enforcement and the theory of unfair justice, the judge's considerations are to pay attention to the absence of justification and pardon and to impose a prison sentence of 4 years.